2015
DOI: 10.1016/j.quaint.2015.01.047
|View full text |Cite
|
Sign up to set email alerts
|

The role of orbital forcing in the Early Middle Pleistocene Transition

Abstract: The Early-Middle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 70 publications
(75 reference statements)
0
37
0
3
Order By: Relevance
“…427 After 0.9 Ma, the TEX 86 and U K 37 '-derived temperatures at Site 1087 converged, and SSTs 428 warm by 2° C between 0.6 and 0.0 Ma. This increase was superimposed upon large amplitude 429 variations in all the proxy records (Figures 3; 4), which occurred at the same time as the onset of the 430 quasi-100-kyr glacial-interglacial cycles that mark the Early Mid-Pleistocene Transition (EMPT) 431 (Maslin and Brierley, 2015). After the EMPT, the pattern of glacials and interglacials changes to a 432 tripartite mode composed of an interglacial, a glacial and a full glacial (Maslin and Brierley, 2015).…”
Section: Late Pliocene (35-30 Ma) 291mentioning
confidence: 96%
See 1 more Smart Citation
“…427 After 0.9 Ma, the TEX 86 and U K 37 '-derived temperatures at Site 1087 converged, and SSTs 428 warm by 2° C between 0.6 and 0.0 Ma. This increase was superimposed upon large amplitude 429 variations in all the proxy records (Figures 3; 4), which occurred at the same time as the onset of the 430 quasi-100-kyr glacial-interglacial cycles that mark the Early Mid-Pleistocene Transition (EMPT) 431 (Maslin and Brierley, 2015). After the EMPT, the pattern of glacials and interglacials changes to a 432 tripartite mode composed of an interglacial, a glacial and a full glacial (Maslin and Brierley, 2015).…”
Section: Late Pliocene (35-30 Ma) 291mentioning
confidence: 96%
“…This increase was superimposed upon large amplitude 429 variations in all the proxy records (Figures 3; 4), which occurred at the same time as the onset of the 430 quasi-100-kyr glacial-interglacial cycles that mark the Early Mid-Pleistocene Transition (EMPT) 431 (Maslin and Brierley, 2015). After the EMPT, the pattern of glacials and interglacials changes to a 432 tripartite mode composed of an interglacial, a glacial and a full glacial (Maslin and Brierley, 2015). At 433 ODP Site 1087 productivity decreases, and the abundance of the Agulhas Leakage indicator 434 foraminifera, G. menardii, increases during the 'full glacial' portion of the deglaciation over the last 435 1.2 Ma (Caley et al, 2014(Caley et al, , 2012.…”
Section: Late Pliocene (35-30 Ma) 291mentioning
confidence: 97%
“…However, recent studies have shown that orbital forcing and the ice-albedo feedback cannot explain key features of the glacial-interglacial oscillations such as the observed magnitudes of global temperature changes, the skewness of temperature response (i.e. slow glaciations followed by rapid meltdowns), and the midPleistocene transition from a 41 Ky to 100 Ky cycle length [103][104][105]. The only significant forcing remaining in the present paleo-climatological toolbox to explicate the Pleistocene cycles are variations in greenhousegas concentrations.…”
Section: Citation: Nikolov N Zeller K (2017) New Insights On the Phymentioning
confidence: 99%
“…Records of EEP SST can be divided at the mid‐Pleistocene transition (MPT, ~1.0–0.8 Ma), a period when Pleistocene marine δ 18 O records progressively shifted from being dominated by oscillations at the 41 kyr periodicity to a more asymmetric longer‐term rhythm with colder glacials; this climate shift is likely not the result of a regime change in orbital insolation forcing but rather either the gradual movement over a threshold that changed internal Earth system feedbacks or a more abrupt climate event [e.g., Pisias and Moore , ; Elkibbi and Rial , ; Clark et al ., ; Kitamura , ]. In light of the lack of an obvious insolation‐related mechanism for this MPT shift, possible Earth system explanations include changes in the behavior of ice sheets [ Imbrie et al ., ; Clark and Pollard , ; Gildor and Tziperman , , ; Clark et al ., ; McClymont et al ., ] and/or periodic oceanic carbon sequestration and release [e.g., Schmieder et al ., ; Toggweiler et al ., ; Watson and Naveira Garabato , ; Kemp et al ., ; Sigman et al ., ; Pena and Goldstein , ; Maslin and Brierley , ]. Tropical ocean dynamics could play a role in either of these factors; for instance, cooling tropical Pacific SST prior to 0.9 Ma could be linked to a glacial p CO 2 decline or could have been a precondition for the expansion of ice sheets [ McClymont et al ., ].…”
Section: Introductionmentioning
confidence: 99%